Prozessoptimierung in der Langzeitpflege durch die Implementierung der stationären Tourenplanung im Bezug zur Entlastung von Pflegepersonal. - Knape, Claudia; Teubner, Andreas; Jager, Antje (HeilberufeSCIENCE, 2016)
Background: Process optimization allocates complex work procedures to limited staff resources, taking economic aspects into consideration. One form is the implementation of in-house route planning. Objective: In this context, the implementation of the in-house route planning process, taking into consideration stress and relief factors, is to be determined to derive future improvements. Methods: To solve the problem, six semi-structured interviews for the implementation of in-house route planning were conducted with residential area managers. Furthermore, there was a voluntary and anonymous staff survey in an old people's nursing home to identify stress and relief factors. The returns quota was about 48 % ( n = 48). Results: The results of the six single interviews showed that the optimization process was not completely implemented owing to insufficient business targets and inadequate communication between the nursing management and residential area management. According to the staff survey, most stress is caused by work organization, especially regarding break arrangements and the independent determination of work units..Furthermore, a significant connection between variable age and frequent time pressure and between professional qualification and frequent time pressure was apparent ( p ≤ 5 %). Discussion: As a result of the methodology applied, the time allowances in in-house route planning could be identified as troubling. Stress caused by work organization has therefore addtionally increased, resulting in long-term stress. Conclusion: Moreover, the pre-defined times in in-house route planning should take on a subordinate role to reduce long-term stress factors.